Intellectual capital and public sector performance - Kamaruddin, Kardina; Abeysekera, Indra (Emerald, 2013)
This study investigated the management of intellectual capital (observed as internal capital, external capital, and human capital) as a tool for non-financial organizational performance (observed as effectiveness, efficiency, and reputation). The study used self-administered survey questionnaires to collect data on both the intellectual capital and non-financial organizational performance aspects of the Malaysian public sector which has undergone a radical transformation through New Public Management Reforms. The total number of participants was 1,092 covering the three levels (federal, state, and the local governments) of the government. The results of the survey questionnaire were analyzed using a multivariate Structural Equation Model, and revealed that there is a significant and positive relationship between intellectual capital and performance. Findings provide useful input to policymakers into the review of the relevant intellectual capital resources, and on improving the public sector performance. From a practical perspective, one way of increasing the level of public sector performance is to tie performance to intellectual capital.
Keywords: Administrative agencies -- Evaluation.; Intellectual capital.; Performance standards.; elektronické knihy; electronic books